Clarifying the origin of Houzao - Zhongzhen Zhao; Eric Brand; Hiu Yee Kwan; Quanbin Han; Mengjia Zhou (BMC, 2018)
Abstract Background Houzao (bezoar) is a valuable imported Chinese medicine that is commonly used as a pediatric medicine to transform phlegm. There are mainly two types of Houzao, "Southeast Asian Houzao" and "Indian Houzao". "Indian Houzao" is the dominant commercial product accounts for over 95% of the actual utilization in the market. However, its origin, formation, composition, efficacy and pharmacology remain unclear. Therefore, we have conducted on-site investigation to clarify the origin of Indian Houzao. We have dissected one male and one female domestic Indian goats in the pastoral areas of Telangana province in south-central India. Our results show: 1.Indian Houzao originates from Indian goats rather than from macaques; it comes from goats and not sheep, and is not limited to female goats.2.The exact location of the bezoar is in the caecum and not stomach or intestines.3.Acacia seeds serve as the primer to induce the formation of bezoar in the caecum.4.The formation and development of the bezoar are closely related to the special local ecosystem and food chain. These goats eat the shoots of Acacia nilotica, and also other local plants in the families of Euphorbiaceae, Rutaceae, Combretaceae, etc.5.It takes around 120 days for the bezoar to be fully developed inside the goat. Many goats are slaughtered in the Indian festival Dusserah from October to December.Indian Houzao is the bezoar from the caecum of Indian goats, formed in response to pathological stimulation, and is the dominant commercial form of "Houzao" on the market. It has been used historically. It has natural supply source. Producers can guarantee a sustainable supply of the bezoars for the market. The usage of bezoar as medicine is also acceptable from the perspective of animal protection. Many patients and people in the Chinese medicine field do not know Indian Houzao comes from Indian goats but from other unsustainable animal sources, which has a negative influence on its actual use and scientific research potential. Conclusion Our study has clarified the origin of Indian Houzao, which can help to further develop Indian Houzao for the treatment of diseases.